Find (f*g)(x) when f(x)=sqr x+3/x and g(x)= sqr x+3/2x

A. (f*g)(x)=x^2+6x+9/2x^2
B. (f*g)(x)=sqr x+3/2x^2
C. (f*g)(x)=x+3/2x^2
D. (f*g)(x)=x^2+9/2x^2

1 answer

To find (f*g)(x), we need to multiply f(x) and g(x).

f(x) = sqrt(x+3)/x
g(x) = sqrt(x+3)/2x

(f*g)(x) = f(x) * g(x)
= (sqrt(x+3)/x) * (sqrt(x+3)/2x)
= (sqrt(x+3) * sqrt(x+3)) / (x * 2x)
= (x+3) / (2x^2)

So, the answer is (f*g)(x) = (x+3) / (2x^2), which is option C.
Similar Questions
  1. Given the function: f(x) = x^2 + 1 / x^2 - 9a)find y and x intercepts b) find the first derivative c) find any critical values
    1. answers icon 1 answer
  2. Given the function: f(x) = x^2 + 1 / x^2 - 9a)find y and x intercepts b) find the first derivative c) find any critical values
    1. answers icon 0 answers
  3. Let equation of an hyperbola be y^2-4x^2+4y+24x-41=0a. Find the standard form b. Find the center c. Find the vertices d. Find
    1. answers icon 0 answers
  4. For the following graph:a. Find the domain of f. b. Find the range of f. c. Find the x-intercepts. d. Find the y-intercept. e.
    1. answers icon 1 answer
more similar questions